DEVELOPMENT OF THE SWARA AUGMENTED REALITY APPLICATION FOR WASTE SORTING EDUCATION IN ELEMENTARY SCHOOLS - Syahbaniar Rofiah; Endang Retnoningsih (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2026)
The prevailing issue of suboptimal waste management significantly contributes to environmental pollution. While early environmental education is crucial for instilling the habit of waste sorting, conventional methods often fail to engage elementary school students. To address this, this study developed an innovative learning medium integrating Augmented Reality (AR) to provide a more interactive and enjoyable learning experience. This research employed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Initial Analysis identified user needs, leading to the Design of an application incorporating AR for interactive visualization for waste classification and marker creation. This development resulted in the "Smart Waste Sorting Augmented Reality" (SWARA) learning medium. Implementation involved trials in elementary schools in Bekasi Regency, with sampling determined by simple random sampling and the Slovin formula. The developed SWARA application features three waste marker categories: organic, Inorganic, and hazardous waste. Trial results demonstrated that the application successfully improved students' waste sorting accuracy and enhanced their knowledge of recycling. Evaluation using the User Experience Questionnaire (UEQ) across six main scales (Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, Novelty) showed an overall average result in the "Good" category. The highest scores were for Perspicuity (1.78) and Efficiency (1.74), while the lowest was Novelty (1.15), though still within the good range. The findings demonstrate that AR based learning significantly enhances students’ conceptual understanding, engagement, and practical skills in waste sorting compared to conventional learning methods.